The electron microscopy of crystalline polymers - Grubb, D; Grubb, D. T. (1970)
﻿ This thesis describes the micro-structure of crystalline polymers, particularly as revealed by electron microscopy, and also the effect of the electron beam on the radiation sensitive specimens under various conditions. Polymer single crystals grown from dilute solution were used for the radiation damage studies, as they are thin (100 andAring;), and a single preparation may contain 108 crystals of uniform properties. Preparations of polyethylene (PE), polyoxymethylene (POM), poly-4-methylpentene-1 (P4MP), nylon 6 and polyethylene oxide were characterized in the transmission electron microscope, confirming previous work for the most part. The scanning electron microscope, operating in its normal mode, showed even the thinnest single crystals clearly, when they were sedimented onto a metal coated substrate. Attempts to observe the 3-D pyramidal structure of PE single crystals were unsuccessful. The crumpling seen when crystals floating on glycerol, or freely suspended from a fine mesh, are irradiated in an electron microscope indicates that even if the structure were preserved, by freeze drying or however, it would be difficult to observe. Thicker, complex, crystals seemed more stable in the scanning electron microscope, and cannot be seen well in the transmission microscope. A chart recorder, picoammeter and special faraday cup were fitted to a Siemens Elmiskop 1 for accurate beam current measurements, and dynamic recording of the varying intensity of polymer crystal images. Reproducible curves for the variation of intensity of one spot in the diffraction pattern were obtained for POM and PE. There was a period, p, of very variable intensity, followed by an exponential decay. The very variable intensity is due to the diffraction contrast of detail, so after p no information could be gained from the crystal, although the diffraction pattern shows it to be largely crystalline at that point. For the particular preparations described, at 100 kV. This thesis describes the micro-structure of crystalline polymers, particularly as revealed by electron microscopy, and also the effect of the electron beam on the radiation sensitive specimens under various conditions. Polymer single crystals grown from dilute solution were used for the radiation damage studies, as they are thin (100 Å), and a single preparation may contain 108 crystals of uniform properties. Preparations of polyethylene (PE), polyoxymethylene (POM), poly-4-methylpentene-1 (P4MP), nylon 6 and polyethylene oxide were characterized in the transmission electron microscope, confirming previous work for the most part. The scanning electron microscope, operating in its normal mode, showed even the thinnest single crystals clearly, when they were sedimented onto a metal coated substrate. Attempts to observe the 3-D pyramidal structure of PE single crystals were unsuccessful. The crumpling seen when crystals floating on glycerol, or freely suspended from a fine mesh, are irradiated in an electron microscope indicates that even if the structure were preserved, by freeze drying or however, it would be difficult to observe. Thicker, complex, crystals seemed more stable in the scanning electron microscope, and cannot be seen well in the transmission microscope. A chart recorder, picoammeter and special faraday cup were fitted to a Siemens Elmiskop 1 for accurate beam current measurements, and dynamic recording of the varying intensity of polymer crystal images. Reproducible curves for the variation of intensity of one spot in the diffraction pattern were obtained for POM and PE. There was a period, p, of very variable intensity, followed by an exponential decay. The very variable intensity is due to the diffraction contrast of detail, so after p no information could be gained from the crystal, although the diffraction pattern shows it to be largely crystalline at that point. For the particular preparations described, at 100 kV; Please see the pdf for full abstract.